Being a guest: perspectives of an extended hospitality approach - Pechlaner, Harald; Nordhorn, C.; Poppe, X. (Emerald Group Publishing Ltd., 2016)
Purpose: This paper aims to deduce and present an extended hospitality approach. In developed countries, hospitality is increasingly linked to tourism; in times of migration and increased refugee flows, the accompanying social, economic and political determining factors play a more prominent role, necessitating a new view of hospitality. This study aims to extend the domain of tourism in hospitality by including aspects related to asylum seekers and to combine it with topics regarding welcome culture, service quality and relational quality. The paper explores the question concerning whether, and in which ways, the various sectors may learn from each other. Design/methodology/approach: To expand this new research area and to take the exploratory nature of the research aim into consideration, a qualitative approach was chosen. Fourteen qualitative interviews with experts from the tourism and industry sectors and organizations linked with asylum seekers were conducted; the interviewees were chosen by purposeful sampling, according to knowledge and diversity criteria. GABEK was used as a qualitative research strategy, which involves theories of a phenomenological and linguistic nature. This method allows for a more holistic approach to the complex nature of the topic through the collection of perceptions resulting from open qualitative interviews and a keyword-based analysis. Findings: The paper presents a model for an extended hospitality approach, as hospitality should not be limited to its connection with tourism matters. Refugees as well as tourists rely on the friendliness and the welcoming nature (hereafter: “welcome culture”) of a host country. The tourism industry can stand to improve its unconditional hospitality toward refugees — the comprehension and understanding of different cultures and values is an important aspect of welcoming new arrivals in the local surroundings, be they tourists, migrants or refugees. Research limitations/implications: As stated above, a qualitative research approach was chosen with the intent to open the research field toward an extended hospitality approach. Therefore, future research must focus on testing the results for application in a more general context. The study was also limited insofar as the conduction of research took place in Bavaria alone. Practical implications: As stated above, a qualitative research approach was chosen with the intent to open the research field toward an extended hospitality approach. Therefore, future research must focus on testing the results for application in a more general context. The study was also limited insofar as the conduction of research took place in Bavaria alone. Originality/value: This paper combines different access points to hospitality in a new form.